PROBLEMS OF AGRICULTURE OF THE REPUBLIC OF SERBIA AND MEASURES TO OVERCOME CRISIS - Pejanović, Radovan; Cvijanović, Drago; Njegovan, Zoran; Tica, Nedeljko; Živković, Dragić (Economics of Agriculture, 2018)
The authors discuss the current issues of agriculture of the Republic of Serbia, on the occasion of the world economic crisis, which negatively reflects on the agriculture. Agriculture is already in a long-term crisis, which manifests through its permanent unfavorable economic position. The authors distinguished four groups of problems: unfavorable structure of land possession and desorganisation of commodity producers; inordinateness of agricultural market; absence of competitivness; inadequate role of the state. The authors suggest measures and actions to stop the negative trends in agriculture.